Study of ⁴He(γ, pn)d reaction mechanism for Eγ up to 100 MeV - Glaznev, M.S.; Gorbenko, E.S.; Bespalov, A.L.; Murtazin, R.T.; Khodyachikh, A.F. (Вопросы атомной науки и техники, 2013)
Using a spectrometer based on a diffusion chamber, which is placed in the magnetic field, the ⁴He(γ,pn)d reaction was researched in the energy range from the reaction threshold up to 100 MeV. Nucleons differential cross sections, angular and energy correlation functions of the reaction products were measured. The structure which wasn't observed previously is detected in the deuteron kinetical energies distribution of events. Possible γ-quanta absorbtion by nucleus mechanisms are discussed.